1997
DOI: 10.1001/archsurg.1997.01430290093019
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Gastrointestinal Intramucosal pH Is a Poor Guide to Tolerable Levels of Anemia During Isovolemic Hemodilution in a Canine Model of Coronary Stenosis

Abstract: Myocardium compromised by coronary stenosis is more sensitive to normovolemic hemodilution-induced ischemia than the normally perfused gut mucosa. This limits the potential utilization of the measurement of gastrointestinal intramucosal pH as a guide to tolerable levels of anemia in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…32 Finally, Layland et al showed that intramucosal pH was maintained during normovolemic hemodilution, despite reaching hemoglobin of 8.2 Ϯ 1.4 g/dL. 33 However, no previous study has specifically addressed the issue of ⌬PCO 2 behavior in supply dependency-induced hemodilution.…”
Section: Intramucosal-arterial Pco 2 Gap In Anemic Hypoxiamentioning
confidence: 99%
“…32 Finally, Layland et al showed that intramucosal pH was maintained during normovolemic hemodilution, despite reaching hemoglobin of 8.2 Ϯ 1.4 g/dL. 33 However, no previous study has specifically addressed the issue of ⌬PCO 2 behavior in supply dependency-induced hemodilution.…”
Section: Intramucosal-arterial Pco 2 Gap In Anemic Hypoxiamentioning
confidence: 99%
“…An increase in C02 partial pressure is considered to indicate splanchnic hypoperfusion. During normovolemic haemodilution, however, splanchnic and gastric perfusion actually increases [13-151 and Layland et al [16] have shown that in dogs with one coronary stenosis, myocardial ischemia occurs at higher haemoglobin levels than gastrointestinal intramucosal acidosis. Gastric tonometry thus may not be ideally suited to monitor the adequacy of 0 2 delivery during haemodilution and acute anaemia.…”
mentioning
confidence: 99%